Effective teaching for increase higher-order thinking skills (hots) in education of elementary school - Z Misykah; A A Adiansha (Pascasarjana Universitas Pendidikan Indonesia, 2018)
Teaching learners to have High-Level Thinking Skills is a challenge in the 21st century, this is because High-Order Thinking Skills (HOTS) becomes a very important part inthe world of education, it is expected when students have High-Level Thinking Skills (HOTS)can improve the competitiveness of labor, productivity, added value, and opens jobopportunities, thereby High-Level Thinking Skills become very interesting topics to discuss. High-Level Thinking Skills (HOTS) can be trained through Mathematics lessons. This study aims to explain the aspects that must be considered in support of participants educate, theseaspects include learning strategies, assessment and classroom enviroment. This research usesliterature method, literature method is a method that uses library sources, articles, journals,books or others as reference source in this writing research.